Pengaruh Pelatihan Kewirausahaan dan Efikasi Diri Terhadap Minat Berwirausaha - Rahman, Rahman; Dewi Rakhmawati; Grace Evelina Buji; Hidayati, Hidayati (FKIP, Universitas Palangka Raya, 2024)
This study aims to determine the effect of entrepreneurship training and self-efficacy on community entrepreneurial interest. This research was conducted in kereng bengkirai village. The source of data in this study is the community of Kereng Bangkirai village. The research method used in this research is quantitative research methods. While the approach that researchers do in this study is with a descriptive approach. The population in this study were all participants who participated in the training while the sample in this study amounted to 20 people. Based on the results of research that has been done, it is known that there is an influence of entrepreneurship training and self-efficacy on the entrepreneurial interest of the Kereng Bangkirai village community from the results of the F test (simultaneously) which amounted to 86.930. Furthermore, the value of the Coefficient of Determination is 0.911, meaning that the results above there is an influence of variables XI and X2 on variable Y by 91.1%, and the remaining 8.9% is influenced by other factors outside this study.